International migration and human rights : the global repercussions of U.S. policy - Martínez, Samuel, 1959- (Global, area, and international archive., 2009)
A multidisciplinary group of scholars examines how the actions of the United States as a global leader are worsening pressures on people worldwide to migrate, while simultaneously degrading migrant rights. Uniting such diverse issues as market reform, drug policy, and terrorism under a common framework of human rights, the book constitutes a call for a new vision on immigration.